How to Reflexively Decentre EU Foreign Policy: Dissonance and Contrapuntal Reconstruction in Migration, Religious and Neighbourhood Governance. (20th April 2022) - Wolff, Sarah; Gazsi, David; Huber, Daniela; Fisher‐Onar, Nora
Abstract: This article develops a timely new model for EU foreign policy by advancing the call for a 'decentring agenda', focused on the challenge of inclusive 'reconstruction'. It does so by first staking out an ontological space at the intersection of empirical multiplexity and normative pluriversality. Within this space, it proposes an ethically informed methodological tool: the contrapuntal negotiation of dissonant perspectives on common governance challenges. It then suggests ways to reconstruct analytical and policy‐making processes and outcomes on the basis of mutuality and local empowerment. Using three scales of 'contrapuntality' (micro, meso and macro) to read key empirical sites at the intersection of the EU's internal and external policies (migration, religious and neighbourhood governance), it argues that by decentring in these and further arenas, the EU can seek to become a more reflexive global actor in sync with the ethical and practical demands of our multiplex world.